بناء نموذج رياضي للتنبؤ بتصنيف المشروعات الصغيرة باستخدام التحليل التميزي في بعض المحافظات السورية - العلي, ابراهيم; علوش, ياسر (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف البحث إلى تقديم نموذج مقترح لتصنيف المشروعات الصغيرة إلى مشروعات (خاسرة، متعثرة، ناجحة) باستخدام أسلوب التحليل التمييزي، بغية التعرف على ظروف تلك المشروعات والتنبؤ بتصنيفها قبل إنشائها أو في وقت مبكر من إنشائها، مما يسمح للجهات المسؤولة عنها (أفراد، هيئات، منظمات ....) بالتدخل بغية اتخاذ الإجراءات الكفيلة بالحفاظ عليها وتطويرها. كما يهدف إلى تحديد المتغيرات الأكثر تأثيراً في تصنيف المشروعات الصغيرة. وقد بينت نتائج البحث وجود أثر تصنيفي لمتغيرات عدد العمال(X2) والميزانية الافتتاحية (X3) وعمر المشروع (X4)، والمنافسة في السوق (X7) في درجة تصنيف المشروعات الصغيرة محل الدراسة، ثم تم التوصل لدالتي تمييز لهما قدرة عالية على التمييز بين فئات المتغير التابع، كما تم التوصل لثلاث دوال تصنيفية للمشروعات الصغيرة في حالة (خاسرة، متعثرة، ناجحة). وقد دلّ اختبار جودة النموذج أن صحة تصنيف إجمالي المشروعات بلغ 86.98%، ونسبة التصنيف الصحيح للمشروعات الخاسرة 84.956%، وللمشروعات المتعثرة 84.746%، وللمشروعات الناجحة 88.736%. The aim of the research is to present the proposed model for the classification of small projects into (losing, Stumbling, successful) projects using the method of discriminant analysis, in order to identify the conditions of these projects and to predict their classification prior to their establishment or in an early stage of their, which enables the parties responsible of these project ( persons, establishments, Organizations ...) to intervene in order to take measures sufficient to maintain and develop them. It also aims at identifying the most influential variables in the classification of small projects. The results of the research showed that there was a qualitative effect of the number of workers (X2), the opening budget (X3), the age of the project (X4) and the competition in the market (X7) to taxonomic functions for small projects subject matter of the research. Three taxonomic function groups were achieved in case of (losing, Stumbling, successful). The quality test of the model showed that the validity of the classification of the total projects reached 86.98%, the correct classification of the losing projects reached 84.956%, the Stumbling projects reached 84.746%, and the successful projects reached 88.736%.